PERSEPSI PEMUDA TERHADAP KEGIATAN USAHATANI KELAPA DI DESA KAUDITAN II KECAMATAN KAUDITAN - Jouke Adelheid Punuh; Joachim Noch Karel Dumais; Melsje Yellie Memah (Sam Ratulangi University, 2020)
The objective of this research to find out how young people's perceptions of knowing and doing coconut farming business activities in Kauditan II Village, Kauditan Sub-district, North Minahasa Regency. The research conducted for six months, namely July to December 2019. The data used in this study are primary and secondary data. The research was carried out in Kauditan II Village, Kauditan District, North Minahasa Regency. The choice of location in this study was chosen based on the consideration that the village has coconut farmland. The research lasted for six months, from July to December 2019. Sampling was carried out deliberately on 37 young men whose parents engaged in coconut. The data needed in this study are primary data and secondary data. Primary data collected through interviews is carried out using a list of questions. Secondary data was obtained through documents and literature research results as well as data and information available at the Kauditan II Village Office. The data analysis technique used is the analysis and descriptive techniques using a Likert Scale measurement. The results showed that the youth agreed to do and understand the activities of coconut farming. The statement of youth to know postharvest tends to be higher, that is to agree because postharvest work is considered easier than other farming activities while the lowest score of the statement of youth wants to harvest on coconut trees because young people do not want to do coconut climbing activities that require special techniques.*eprm*